Barriers of utilisation of dental services among children and adolescent: A systematic review - Farlina, Avlien; Maharani, Diah Ayu (Padjadjaran Journal of Dentistry, 2018)
Introduction: Underutilisation of dental services among children and adolescent is a worldwide problem that increases caries prevalence. Younger children are less likely to receive dental care and, thus, experience oral diseases more often. This systematic review was aimed to explore the barriers of utilisation of dental services among children and adolescent. Methods: The literature search was conducted in the electronic database of Pubmed©/Medline©. The literature exclusion criteria were adults and qualitative study. Keywords were verified in MeSH. Boolean “AND” and “NOT” was used to specify the search. Twenty-four literature were filtered from Pubmed©, and twenty-three literature fit the inclusion criteria. Result: The result revealed that low-income families, minority ethnic, and disability condition have lower dental care utilisation. Conclusion: The identified potential determinants of oral health and dental care utilisation among children and adolescent are economic barriers, uninsurance, and availability of dental service providers.Keywords: Dental care, dental services, utilisation, barrier, children, adolescent.